The Organizing Free Play or Creative Play in Science Corner Based on the Concept of High-Scope to Promote Rational Thinking Skills for Early Childhood - Kongprom, Pawinee; Kusolsong, Sroungporn (Suan Dusit Graduate School Academic Journal, 2022)
This research aimed to study the organization of free play or creative play in science corner based on the concept of High-Scope and to compare rational thinking skills of preschool children before and after the activities. The sample group used in this study were pre-primary boys and girls aged 4-5 years, studying Kindergarten Year 2, semester 2, Academic Year 2020, Ban Tha Phon (Tha Phon Wittayakarn) School, Phetchabun Primary Educational Service Area Office, District 1. The sample consisted of 27 students, including 10 males and 17 females, obtained by simple random sampling by using the school name as the random sampling unit. The tools used in the research included 1) 20 plans of free play or creative play in science corner based on the concept of high-scope for early childhood. 2) The handbook of 20 activities of free play or creative play in science corner based on the concept of high-scope for early childhood. 3) The 2 sets of evaluation form for rational thinking skills of early childhood. The experiments were conducted according to the One-Group Pretest-Posttest Design research model and the data were analyzed using mean scores, variance and standard deviation. The results of hypothesis testing by using Dependent t-test revealed that 1) The activity quality of free play or creative play in science corner based on the concept of high-scope for early childhood was found at 4.21 ( x̅ = 4.21), which was at the high level. The results showed that the time and activities were appropriate. 2) The overall pre-activity scores of rational thinking skills for preschool children was averaged at 13.56 (S.D. = 2.77), the post-activity was averaged at 16.56 (S.D. = 2.15), resulting in higher development scores with an average of 3.00 (S.D. = 1.14). This finding indicated that after the activities, early childhood children had higher rational thinking skills than before the activities. This was consistent with the hypothesis at the statistical significance level of .05.